Establishment and characterization of a novel murine model of pancreatic cancer cachexia. Issue 5 (20th July 2017) - Michaelis, Katherine A.; Zhu, Xinxia; Burfeind, Kevin G.; Krasnow, Stephanie M.; Levasseur, Peter R.; Morgan, Terry K.; Marks, Daniel L.
Abstract: Background: Cachexia is a complex metabolic and behavioural syndrome lacking effective therapies. Pancreatic ductal adenocarcinoma (PDAC) is one of the most important conditions associated with cachexia, with >80% of PDAC patients suffering from the condition. To establish the cardinal features of a murine model of PDAC‐associated cachexia, we characterized the effects of implanting a pancreatic tumour cell line from a syngeneic C57BL/6 KRAS G12D P53 R172H Pdx‐Cre +/+ (KPC) mouse. Methods: Male and female C57BL/6 mice were inoculated subcutaneously, intraperitoneally, or orthotopically with KPC tumour cells. We performed rigorous phenotypic, metabolic, and behavioural analysis of animals over the course of tumour development. Results: All routes of administration produced rapidly growing tumours histologically consistent with moderate to poorly differentiated PDAC. The phenotype of this model was dependent on route of administration, with orthotopic and intraperitoneal implantation inducing more severe cachexia than subcutaneous implantation. KPC tumour growth decreased food intake, decreased adiposity and lean body mass, and decreased locomotor activity. Muscle catabolism was observed in both skeletal and cardiac muscles, but the dominant catabolic pathway differed between these tissues. The wasting syndrome in this model was accompanied by hypothalamic inflammation, progressively decreasing brown and white adipose tissue uncoupling protein 1 ( Ucp1 ) expression, and increased peripheral inflammation. Haematological and endocrine abnormalities included neutrophil‐dominant leukocytosis and anaemia, and decreased serum testosterone. Conclusions: Syngeneic KPC allografts are a robust model for studying cachexia, which recapitulate key features of the PDAC disease process and induce a wide array of cachexia manifestations. This model is therefore ideally suited for future studies exploring the physiological systems involved in cachexia and for preclinical studies of novel therapies.